Factors Causing Stunting and the Value of Economic Losses Due to Stunting in Ketapang Regency - Tri Kurniasih, Albertin; Rosyadi, Rosyadi; Bariyah, Nurul (Journal of World Science, 2024)
This research aims to examine the influence of the factors that cause stunting and the value of economic losses due to stunting in Ketapang Regency by using the factors that cause stunting that are studied, namely food security, social environment, health environment, and residential environment. The method used in this research is descriptive quantitative research. The population used was 88 people with stunted children and 30 people with non-stunted children. The data analysis technique used is the chi-square test statistical analysis program facility using SPSS. The results of this study show that there is a significant relationship between the social environment, social environment, and health environment in the incidence of stunting in the Ketapang district. However, the residential environment has an insignificant relationship with stunting in Ketapang Regency. Moreover, the economic loss caused by stunting, assuming a decrease in productivity of 2 percent to 9 percent, is estimated to range from 1 percent to 10.8 percent of Ketapang's GRDP, or approximately 200 billion rupiah to 1.8 trillion rupiah, thereby underlining the urgency for targeted interventions and policy initiatives to address this issue effectively.